Analisis Risiko Pembangunan Kapal Bertenaga Listrik dan Surya Untuk Mendukung Net Zero Emisi - Hendra Palebangan; Muhajirin Muhajirin; Iskendar Iskendar; Dewi Kartikasari (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Vehicle electrification is becoming a growing trend in the transportation industry due to environmental concerns. Therefore, various global efforts are being made to develop electric-driven ships using environmentally friendly energy sources such as batteries. In the implementation of electric and solar-powered shipbuilding, there is always the potential for delays in completion. This is very detrimental to shipyard owners and even ship owners because it is not to the initial plan. Shipyard owners and shipowners must bear greater or unexpected costs due to delays in work. Other risks also have the potential to arise when electric and solar-powered ships are completed until operation. Delays in the completion of electric and solar-powered shipbuilding can be caused by various things. Through this research, the risk analysis of the development of the electric and solar-powered ship industry is discussed in terms of several aspects, namely market, legal, technical, socio-economic environmental, and financial aspects.